KADAR ASAM AMINO ARGININ SEMEN TIKUS PUTIH JANTAN SETELAH DIBERI TANIN DAUN BELUNTAS SEBAGAI SUMBER BELAJAR - Rr. Eko Susetyarini (Universitas Sebelas Maret, 2014)
Abstract - Beluntas leaves contain a variety of active compounds, one of the active compounds, namely tannins. Beluntas leaf tannins can reduce sperm fertilization potential of white rats (Susetyarini, 2010a) and decrease the number of white rat spermatogenic cells (Susetyarini, 2012). However, in these studies have not examined the role of tannins in changing levels of arginine cement white male rats. This aims, administration beluntas leaf tannins in influencing the levels of arginine cement white male rats. This type of research is the experiment with the following treatments: a control group (non-treated) and group treated leaf tannins beluntas. Giving beluntas leaf tannins administered orally as much as 0.8 ml (an effective dose of tannins in inhibiting fertilization of previous research) to white rats once daily for 49 +3, 49 +16, 49 +26, 49 +36, 49 +49 days. Observations were made according to treatment, white rat vas deferens dissected and taken to obtain cement rats. Analysis of the amino acid arginine levels using HPLC. Data were analyzed using ANOVA. The results showed that the effect of tannin There beluntas leaves the amino acid levels arginin white male rats (p <0.05). The control group without treatment giving the average levels of the amino acid arginine 1375.5 mg/100g and the group treated leaf tannins beluntas showed no decrease in the levels of the amino acid arginine of white male rats. The results of the study can be used as a learning resource for students of biology for Animal Reproduction course. Keywords: Beluntas leaf tannins, levels of arginine cement, white male rats